MAKNA RELASI TRADISI BUDAYA MASYARAKAT MADURA DALAM PERSPEKTIF ONTOLOGI ANTON BAKKER DAN RELEVANSINYA BAGI PEMBINAAN JATI DIRI ORANG MADURA - Ainur Rahman Hidayat (Jurnal Filsafat "WISDOM", 2013)
Every Maduranese has relation as core structure in itself with the characteristics of relation meaning being different from the other ones and among other thing actualized in its folks. The objectives of research are firstly, to formulate relation meaning in Madura folks of ontological transcendental structure; secondly, to formulate essence of relation in Madura folks of ontological transcendental norm; thirdly, to formulate relevance meaning of relation in Madura folks as main principle to develop Madura identity. This research was a library research with the Anton Bakker’s ontology as the formal object and Madura folks as the material object, that is to say, carok (homicide), rokat tase’ (fishermen ceremonials), and samman (Islamic recitals). This research came to conclude that relation of Madura folks in ontological transcendental structure signifies based socio-culture. Madura folks centered upon unanimity rule of social life, that is, relationship with each other, nature, and God. Unanimity rule aspect is presented and made one of balancing Madura folks. The relation is the starting and end points of reality in Madura folks, which harmony and disharmony are served as ontological transcendental norm. Relevance of relation in Madura folks as main principle to develop Madura identity constitutes standpoint in internalization and crystallization of Madura identity. The relation as starting point means that the result of development and perpetuation of Madura identity is proceed from relation meaning as main principle. The relation as end point means that development, elaboration, and perpetuation of Madura identity are returned to relation meaning as main principle.